Dive wiggles as a proxy of prey consumption in krill-feeding penguins - Oosthuizen, W. Chris; Schoombie, Stefan; Chimienti, Marianna; Pistorius, Pierre A.; Lowther, Andrew D. (Journal of Experimental Marine Biology and Ecology, 2025)
The dive profiles of pursuit-diving marine predators are often used to infer foraging behaviour, including potential indicators of prey consumption. ‘Wiggles’ are undulations in dive profiles that relate to foraging activity in a variety of marine predators. In penguins, wiggles are sometimes used as a proxy for prey consumption (e.g., catch per unit effort, CPUE), but this relationship remains poorly validated and likely varies with diet. We deployed animal-borne video cameras and depth recorders on chinstrap penguins (Pygoscelis antarcticus; n = 37) and identified over 17,000 euphausiid prey captures - mainly Antarctic krill (Euphausia superba) - during dives deeper than 3 m (n = 2458 dives). Using the video-observed prey captures as a reference, we tested how well various wiggle metrics derived from 1 Hz depth data predicted krill consumption by the penguins. Wiggle metrics generally showed a positive but noisy and highly variable relationship with the number of krill captured per dive, with association strength varying among metrics. While it is tempting to infer detailed foraging behaviours from dive wiggles (including ‘bottom distance’ generated by the R package diveMove), our results show: (1) notable rates of foraging – non-foraging dive misclassification; (2) only moderate agreement between CPUE estimated from wiggle counts and video observations; and (3) imprecise predictive models of actual prey consumption. While wiggle analyses offer some insight into prey consumption of krill-feeding penguins, our results suggest that alternative methods (e.g., acceleration-based indices) are needed to obtain more robust quantitative estimates of prey consumption.
Keywords: Sør-Orknøyene; Sørishavet; biologging; marin biologi; marin økologi; pingviner; sjøfugler

Bout time for krill: contrasting Adélie penguin foraging behaviour during years of high and low krill availability - Riaz, Javed; Machado-Gaye, Ana Laura; Chimienti, Marianna; Kato, Akiko; Ropert-Coudert, Yan; Alegría, Nicolás; Barbosa, Andrés; Soutullo, Alvaro (Animal Behaviour, 2025)
Understanding how marine predators structure and adjust their foraging in response to prey field characteristics is a longstanding objective in marine ecology. This is particularly challenging in Southern Ocean ecosystems, where logistical and financial constraints hinder assessment of predator foraging and prey field information at relevant spatial and temporal scales. Here, we examine how Adélie penguins, Pygoscelis adeliae, a key Southern Ocean indicator species, perform and organize their foraging behaviour during two contrasting years of krill (Euphausia superba) abundance. Using multiyear krill acoustic data from King George Island in the West Antarctic Peninsula (WAP), we assess broad seasonal conditions in krill availability. We also analyse a suite of penguin biologging data (spatial location, dive and accelerometry-derived activities) during the same period to identify broad behavioural differences in their bout-diving activity, a classical measure of the temporal organization of foraging in diving predators. During years of high krill abundance and availability, penguins performed shorter dive bouts (consisting of shallower and shorter-duration dives), which were more concentrated in time and space. Despite these differences in bout structure, prey capture attempts occurred at the same rate within bouts. These findings challenge traditional interpretations assuming that increased bout durations (and related proxies of prey capture effort) signal increased krill patch abundance and profitability. Although additional data are required to understand the full scope of penguin bout diving and krill prey field associations, our work improves understanding of penguin behavioural variation and provides insights into how foraging behaviours could potentially be used to interpret krill availability at predator- and management-relevant scales.
Keywords: Sørishavet; ekkolodd; krill; marin biologi; marin økologi; marine økosystemer; matauk; pingviner; plankton

Investigation on morphological and molecular fingerprints of penguin brain using label-free optical imaging and spectroscopic techniques - Bhatt, Sunil; Verma, Ashwani Kumar; Dastidar, Prabir G.; Kumar, Punit; Thapa, Pramila; Jacob, Tony George; Roy, Tara Sankar; Iyengar, Soumya; Kumaran, Senthil; Ahluwalia, Balpreet Singh; Mehta, Dalip Singh (Scientific Reports, 2025)
The morphology and molecular study of the penguin brain are crucial to define its survival in the extreme conditions of Antarctica. The present study focusses on extracting different optical parameters of the penguin brain using label-free optical imaging and spectroscopic techniques. In label-free optical imaging, we have used quantitative phase imaging, which provides morphological information about the neurons in brain tissue, giving the quantitative phase value of 5 to 20 radians corresponding to the 8 µm tissue section. In label-free spectroscopic techniques, we have used autofluorescence and Raman spectroscopy. Autofluorescence spectroscopy provides molecular information about nicotinamide dinucleotide, flavins, lipofuscins, and porphyrins in the brain’s spectral range of 420 nm to 700 nm. Raman spectroscopy provides multiple peaks associated with different molecules in the brain; among them, few signals are observed at approximately 1305 cm−1, 1448 cm−1, and 1661 cm−1, which correspond to vibrational modes indicative of vibrational features within lipids and protein structures, as well as the presence of amide groups within brain tissue constituents. All these techniques provide the microscopic and molecular fingerprint of the penguin brain, which can be useful for understanding penguin’s anatomical, physiological, and social behavior.
Keywords: Antarktis; anatomi; biofysikk; biologi; biomarkører; fysiologi; morfologi; nevrologi; pingviner

Dispersal and habitat preference of juvenile emperor penguins—implications for conservation management - Makhado, Azwianewi Benedict; Crawford, Robert J. M.; Dyer, Bruce M.; Masotla, Makhudu; Lowther, Andrew (Royal Society Open Science, 2025)
Seabirds can disperse widely when searching for prey, particularly during nonbreeding periods. Conservation measures predominately focus on protecting breeding colonies, while spatial protection at sea is often based on knowledge of the distribution of breeding adults, despite accumulating evidence that marine habitats used by immature birds sometimes differ from those of adults. Juvenile emperor penguins from Atka Bay, west Dronning Maud Land, Antarctica, tracked immediately after fledging performed long migrations to the northern extents of the Convention for the Conservation of Antarctic Marine Living Resources subareas 48.4 and 48.6. Individuals did not remain long at their northern positions, before commencing a rapid southerly movement to within a few hundred km of the marginal ice zone (MIZ). The initial migratory movement was broadly synchronous across individuals. The southward movement and subsequent change to area-restricted searching were consistent with the MIZ representing a potentially important feeding habitat for juvenile emperor penguins. Spatio-temporal management mechanisms may be beneficial in reducing threats to these young penguins.
Keywords: Dronning Maud Land; biologi; marine økosystemer; ornitologi; pingviner; sjøfugler; telemetri; økologi

Dive wiggles as a proxy of prey consumption in krill-feeding penguins - Oosthuizen, W. Chris; Schoombie, Stefan; Chimienti, Marianna; Pistorius, Pierre A.; Lowther, Andrew D. (Journal of Experimental Marine Biology and Ecology, 2025)
The dive profiles of pursuit-diving marine predators are often used to infer foraging behaviour, including potential indicators of prey consumption. ‘Wiggles’ are undulations in dive profiles that relate to foraging activity in a variety of marine predators. In penguins, wiggles are sometimes used as a proxy for prey consumption (e.g., catch per unit effort, CPUE), but this relationship remains poorly validated and likely varies with diet. We deployed animal-borne video cameras and depth recorders on chinstrap penguins (Pygoscelis antarcticus; n = 37) and identified over 17,000 euphausiid prey captures - mainly Antarctic krill (Euphausia superba) - during dives deeper than 3 m (n = 2458 dives). Using the video-observed prey captures as a reference, we tested how well various wiggle metrics derived from 1 Hz depth data predicted krill consumption by the penguins. Wiggle metrics generally showed a positive but noisy and highly variable relationship with the number of krill captured per dive, with association strength varying among metrics. While it is tempting to infer detailed foraging behaviours from dive wiggles (including ‘bottom distance’ generated by the R package diveMove), our results show: (1) notable rates of foraging – non-foraging dive misclassification; (2) only moderate agreement between CPUE estimated from wiggle counts and video observations; and (3) imprecise predictive models of actual prey consumption. While wiggle analyses offer some insight into prey consumption of krill-feeding penguins, our results suggest that alternative methods (e.g., acceleration-based indices) are needed to obtain more robust quantitative estimates of prey consumption.
Keywords: Sørishavet; biologging; marin biologi; pingviner; sjøfugler; økologi